ANALYSIS OF FACTORS AFFECTING ECONOMIC GROWTH AND POVERTY IN REGENCIES/CITIES OF BALI PROVINCE - Gusti Ngurah Made Satria Sastra Adigunawan; Anak Agung Istri Ngurah Marhaeni (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Poverty remains a serious issue in Indonesia and poses a significant burden, particularly due to the widening gap between the rich and the poor. Based on data from the Bali Provincial Statistics Agency (BPS), Karangasem Regency recorded the highest poverty rate in 2023. The poverty rate affects regional economic performance, highlighting the urgent need to address poverty alleviation efforts in Bali Province. This study aims to: (1) analyze the effects of education level, regional original income (PAD), employment, and investment on economic growth in regencies/cities of Bali Province; (2) analyze the effects of education level, PAD, employment, investment, and economic growth on poverty levels in regencies/cities of Bali Province; and (3) analyze the indirect effects of education level, PAD, employment, and investment on poverty through economic growth. The data used are panel data spanning eleven years, from 2013 to 2023, with a total of 90 observations. The analytical method employed is path analysis with the assistance of SPSS software. The results indicate that education level, PAD, and employment have a positive and significant effect on economic growth. However, investment has a negative and significant effect on economic growth. Furthermore, economic growth, education level, PAD, and investment have a negative and significant effect on poverty levels, while employment does not have a significant negative effect. In addition, education level, local original income (PAD), working population, and investment have an indirect effect on poverty through economic growth. These findings suggest that improving these factors can stimulate economic growth while simultaneously reducing poverty in Bali Province.